A Toponymic Approach to the Wetlands Local History in Sungai Tabuk Keramat Village - Yahya, Daud (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This research aims to uncover the toponymy of Laut and Pantai Rumbia in Sungai Tabuk Keramat village. Using a historical approach, this study explores how early communities interacted with their environment, understood the landscapes they inhabited, and reflected cultural values in place naming. The results indicate that the toponymy of Laut and Pantai Rumbia reflects the social and cognitive construction of space and environment by the community. The diversity of language dialects between the people of Sungai Tabuk Keramat and neighboring villages indicates differences in cultural and historical backgrounds that influence how they interact with the environment and name places. The toponymic analysis in Sungai Tabuk Keramat village contributes to a deeper understanding of local history, cultural landscape, and the social dynamics of Urang Banjar in general.